Knowing the Education Business and Politics of Modern Guanxi Confucian Societies In Bengkalis Island - Halim Dwi Putra (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
Understanding modern Confucius Guanxi politics and business is a new science for business and politics that focuses on trust and mutual benefit between people. This means that people must maintain relationships, share information, solve problems, and seek opportunities to increase value for themselves and for others. This theory also emphasizes the importance of protecting power and complying with applicable business rules and norms. Writing this article is a review of the science of politics and business of Confucian Guanxi both in terms of good and bad. Theory and its applications are very useful for providing different views and perspectives on how to think and do things. However, the lack of politics and business with Bibliometric Analysis using VOSviewer and Publish or Perish. Confucian Guanxi can lead to incorrect understanding and action. For example, the classical theory of economics provides the view that markets will always move toward equilibrium, but this contradicts the fact that most markets in the world are unstable. This has led economists to develop new, more realistic theories. Another negative side of Confucian Guanxi political and business theories is that they can be misinterpreted. Another negative side of Confucian Guanxi political and business theories is that they can be misinterpreted. For example, some people may use psychological theory to claim that people with certain characteristics have limitations that prevent them from achieving their goals. This can lead to assault and exclusion. This theory also has another negative side. They can limit a person's thinking and limit their way of seeing the world. Some people may use theory to support their unfavorable views on certain political and business subjects.